HUBUNGAN KONDISI PENYIMPANAN TERHADAP KUALITAS KADAR IODIUM DALAM GARAM DI TINGKAT PENJUAL YANG BEREDAR DI PASAR TRADISIONAL DI DENPASAR UTARA TAHUN 2017 - Diah Prihatiningsih; Sherly Novitasari (Bali Medika Jurnal, 2017)
Introduction : One of the health problems in Indonesian society that has a huge impact on the survival and quality of human resources is GAKI. One of the basic human needs in daily life is widely used as an additional ingredient in food ingredients as food preservatives such as salted fish, mustard greens, pickled fruits, and the basic manufacture of chemical compounds is salt. The research was to determine the effect of storage process and storage time on iodine content in salt. Method : The research was designed as descriptives quantitative study that conducted in traditional market at North Denpasar. The sample collected was 60 branded salt and unbranded salts. The iodine content was tested using iodometri titration method at Laboratorium Analis Kesehatan STIKes Wira Medika Bali. Data of storage condition was collected from direct measurement and interview with the vendor. The data was analyzed descriptively and analytically. Results : The researched results showed that iodine content of 5 branded and unbranded salts in North Denpasar was 58,98 ± 24,41 ppm. While the storage conditions with the average storage duration time at the traders was 13 days with average temperature of 29,760C and 68,82% humidity.